Identifying familiar risk factors and the practice of self car for precocious detection of the breast cancer in relatives of mastectomized - Isabela Melo Bonfim; Paulo César de Almeida; Iliana Maria de Almeida Araújo; Izabel Cristina Falcão Juvenal Barbosa; Ana Fátima Carvalho Fernandes (Rev Rene)
This is a quantitative research that aims to identify the risk factors and the self care practice for precocious detection of breast cancer in mastectomized patients. For so, 100 family member companions of mastectomized patients, undergoing chemotherapy treatment in a hospital of reference in cancer in the state of Ceará were interviewed. The risk factors identifi ed were: age of fi rst menstruation, lower or equal to twelve years of age; nuliparity, use of oral contraception (CO) and long time use of CO; at risk age group and abortions occurrence. We evidenced that in the struggle against breast cancer, the healthy family accompaniment is of extreme importance for the early detection of the disease. It was so concluded that this stratum of the population has also been contemplated by all the strategies of prevention and precocious detection of breast neoplasms and that the practice of health education be understood under the aspect of a transforming education.